A case report of mental disorder caused by shunt blockage after hydrocephalus surgery - Wu, Jingjing; Li, Wei; Wang, Yaping; Liu, Lijin; Liu, Lanying (Frontiers in Psychiatry, 2024)
IntroductionHydrocephalus is a form of communication hydrocephalus syndrome characterized by ventricular enlargement and normal intraventricular pressure. The primary clinical manifestations include gait disturbances, cognitive dysfunction, urinary incontinence, and either elevated or normal intracranial pressure. This paper presents a case of a mental disorder resulting from inadequate drainage following a ventriculoperitoneal shunt procedure for hydrocephalus. The case report aims to enhance clinicians’ understanding of such organic brain lesions, which are prone to misdiagnosis and inappropriate treatment, thereby improving differential diagnostic skills.Case presentationThis case report describes a 34-year-old male with a 16-year history of depressive disorder, previously managed with 150 mg of venlafaxine daily, 7.5 mg of zopiclone every night, and 2.4 g of piracetam every day. The patient underwent a ventriculoperitoneal shunt procedure for hydrocephalus, leading to the development of a mental disorder attributable to poor drainage from the shunt tube. Initial symptoms consisted of low mood, decreased interest, and cognitive impairment. Despite psychiatric consultation and antidepressant treatment, there was no improvement in his condition. The final diagnosis was an organic mental disorder. Following an increase in shunt drainage and the administration of a low dose of olanzapine, the patient’s psychiatric symptoms showed significant improvement.ConclusionReporting this case seeks to enhance clinicians’ awareness of the psychiatric manifestations of organic brain lesions, expand the differential diagnostic approach for psychiatrists, and improve diagnostic accuracy. Additionally, it emphasizes the need for cautious use of psychiatric medications, appropriate symptomatic management, and timely referral when necessary.